Ventilator Associated Pneumonia a challenge in intensive care unit acquired infection (Bangladesh Journal of Medical Science, 2016)
Background: Ventilator-Associated Pneumonia (VAP) is one of the frequent intensive-care-unit (ICU)-acquired infection. The aetiology of VAP varies with patients profiles and ICU settings. Due to the increasing incidence of multidrug-resistant organisms in ICUs, early and correct diagnosis of VAP is an urgent challenge for an optimal antibiotic treatment. The aim of the study was to assess the incidence of VAP in different patients by various organisms to create a database of the causative agents of VAP, their drug resistance profile in that area.Methodology: A prospective study was done over a period of 12 months in a rural tertiary care hospital enrolling patients undergoing mechanical ventilation (MV) for >48 h. Samples were collected from patients with suspected VAP, cultures were performed on all samples. VAP was diagnosed by the growth of significant pathogens. Combination disk method, EDTA disk synergy (EDS) test and cefoxitin double disc synergy test were performed for the detection of different patterns of drug resistance.Results: Culture positive cases were 52.29% of total. Acinetobacter spp, Klebsiella pneumoniae and Staphylococcus aureus were most frequent pathogen in early-onset VAP, while Pseudomonas spp. and Acinetobacter spp. dominated the list of pathogens responsible for lateonset VAP. Prior antibiotic therapy and hospitalization of five days or more were independent risk factors for VAP by MDR pathogens.Conclusions: This study highlighted high incidence of VAP in our setup. Production of ESBL, AmpC beta-lactamases and metallo beta-lactamases were responsible for the multi-drug resistance of the pathogens causing VAP, implicating the injudicious use of antimicrobial therapy. Combined approaches of rotational antibiotic therapy and education programs might be beneficial to fight against these MDR pathogens to decrease the incidence of VAP.Bangladesh Journal of Medical Science Vol.15(4) 2016 p.588-595